A novel FACTS dynamic stabilisation scheme for stand-alone tidal energy conversion systems. (1st November 2010) - El-Sayed, Mohamed A.H.; Sharaf, Adel M.
Renewable abundant ocean kinetic energy has become increasingly popular as a consequence of strong ecological viable concerns and economical energy solutions in remote island communities. However, the integration of dispersed renewable tidal energy will pose a greater challenge to the power quality of distribution networks in remote areas due to fluctuation of the tidal stream velocity. The paper presents the dynamic simulation of novel stabilisation scheme with coordinated hybrid controller developed by the second author. The tidal energy converter system comprises four key parts. The tidal turbine drives an induction generator and stabilised using the novel modulated power filter MPFC and SVC compensator. The standalone renewable energy scheme feeds a hybrid electric load. The proposed integrated tidal green energy conversion scheme with all subsystems has been digitally simulated using the Matlab/Simulink/Sim-Power software environment. The novel filter compensator scheme with the dynamic error driven hybrid controller developed by the second author was fully validated.